(untitled) (Research, Society and Development, 2022)
This study sought to manage the technological information of agricultural events, in order to enable the efficient use of technology transfer, seeking to generate positive results for rural producers through case studies. The proposal is being developed by the Graduate Program in Biotechnology and Environmental Monitoring, Federal University of São Carlos, Sorocaba Campus, State of São Paulo- Brazil. The procedures used in this work are characterized as applied research. The transfer of technology was analyzed through scientific and technological events carried out in the Project: “Management of technologies generated in projects for the expansion of sugarcane and its environmental effects” with the support of the São Paulo Research Foundation Paulo in the Process: 2017/18918-5. Through the results obtained, it can be inferred that these practices are effective, mainly through digital media, for rural producers, which affirms the need to encourage these technology transfer processes. It is suggested the use of digital media for the dissemination of agricultural events, seeking greater integration of the number of rural producers, aiming at expanding the possibilities of applying the technologies produced and disseminated. With this, digitalization trends follow, minimizing the difficulties of rural producers in monitoring events, contributing to the expansion of borders.